# If ${\sec ^2}\theta + {\tan ^2}\theta + 1 = 2$, then find the value of $\sec \left( { - \theta } \right)$:

A. \[ - 2\]

B. $ - \dfrac{1}{2}$

C. $1$

D. $ \pm 1$

Answer

Verified

366k+ views

Hint : Solve using trigonometric identities.

Given that: ${\sec ^2}\theta + {\tan ^2}\theta + 1 = 2$

Converting the above equation in the terms of Sin and Cos, we get

$

\Rightarrow \dfrac{1}{{{{\cos }^2}\theta }} + \dfrac{{{{\sin }^2}\theta }}{{{{\cos }^2}\theta }} + 1 = 2{\text{ }}\left( {\because \tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}{\text{ and }}\sec \theta = \dfrac{1}{{\cos \theta }}} \right) \\

\Rightarrow \dfrac{{1 + {{\sin }^2}\theta + {{\cos }^2}\theta }}{{{{\cos }^2}\theta }} = 2 \\

\Rightarrow \dfrac{{1 + 1}}{{{{\cos }^2}\theta }} = 2{\text{ }}\left( {\because {{\sin }^2}\theta + {{\cos }^2}\theta = 1} \right) \\

\Rightarrow \dfrac{2}{{{{\cos }^2}\theta }} = 2 \\

\Rightarrow {\cos ^2}\theta = 1 \\

\Rightarrow \cos \theta = \pm 1{\text{ }} \ldots \, \ldots \left( 1 \right) \\

$

We know that, $\cos \left( { - \theta } \right) = \cos \left( \theta \right)$

$\therefore \sec \left( { - \theta } \right) = \sec \left( \theta \right) = \dfrac{1}{{\cos \theta }}$

Put the value of $\cos \theta $ from equation $\left( 1 \right)$, we get

$\sec \left( { - \theta } \right) = \pm 1$

Note: In these types of problems, where there is no direct formula for the given trigonometric terms, one should always try to convert them to some trigonometric terms which have some relation using trigonometric relations and identities so as to make the problem easier to calculate.

Given that: ${\sec ^2}\theta + {\tan ^2}\theta + 1 = 2$

Converting the above equation in the terms of Sin and Cos, we get

$

\Rightarrow \dfrac{1}{{{{\cos }^2}\theta }} + \dfrac{{{{\sin }^2}\theta }}{{{{\cos }^2}\theta }} + 1 = 2{\text{ }}\left( {\because \tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}{\text{ and }}\sec \theta = \dfrac{1}{{\cos \theta }}} \right) \\

\Rightarrow \dfrac{{1 + {{\sin }^2}\theta + {{\cos }^2}\theta }}{{{{\cos }^2}\theta }} = 2 \\

\Rightarrow \dfrac{{1 + 1}}{{{{\cos }^2}\theta }} = 2{\text{ }}\left( {\because {{\sin }^2}\theta + {{\cos }^2}\theta = 1} \right) \\

\Rightarrow \dfrac{2}{{{{\cos }^2}\theta }} = 2 \\

\Rightarrow {\cos ^2}\theta = 1 \\

\Rightarrow \cos \theta = \pm 1{\text{ }} \ldots \, \ldots \left( 1 \right) \\

$

We know that, $\cos \left( { - \theta } \right) = \cos \left( \theta \right)$

$\therefore \sec \left( { - \theta } \right) = \sec \left( \theta \right) = \dfrac{1}{{\cos \theta }}$

Put the value of $\cos \theta $ from equation $\left( 1 \right)$, we get

$\sec \left( { - \theta } \right) = \pm 1$

Note: In these types of problems, where there is no direct formula for the given trigonometric terms, one should always try to convert them to some trigonometric terms which have some relation using trigonometric relations and identities so as to make the problem easier to calculate.

Last updated date: 24th Sep 2023

â€¢

Total views: 366k

â€¢

Views today: 7.66k

Recently Updated Pages

What do you mean by public facilities

Difference between hardware and software

Disadvantages of Advertising

10 Advantages and Disadvantages of Plastic

What do you mean by Endemic Species

What is the Botanical Name of Dog , Cat , Turmeric , Mushroom , Palm

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Summary of the poem Where the Mind is Without Fear class 8 english CBSE

The poet says Beauty is heard in Can you hear beauty class 6 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

What is the past tense of read class 10 english CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE